2015
DOI: 10.1080/15548627.2015.1100785
|View full text |Cite|
|
Sign up to set email alerts
|

BECN1s, a short splice variant of BECN1, functions in mitophagy

Abstract: These authors contributed equally to this work.Keywords: BECN1, BECN1s, mitochondrial depolarization, mitophagy, starvation Abbreviations: Atg, autophagy-related; bp, base pairs; BECN1s, BECN1 short isoform; CCCP, carbonyl cyanide m-chlorophenylhydrazone; EBSS, Earle's balanced salt solution; ECD, evolutionarily conserved domain; GFP, green fluorescent protein; LAMP1, lysosomal-associated membrane protein 1; MAP1LC3/LC3, microtubule-associated protein 1 light chain 3; PtdIns3K, class III phosphatidylinositol 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…102,103 AS converts BECN1 from an inducer of nonselective macroautophagy to a regulator of mitochondriaselective autophagy. 105 BECN1s, a shorter splice variant originating from skipping of exons 10 and 11, selectively localizes in the outer membrane of mitochondria and contributes to mitophagy in response to starvation or mitochondrial membrane depolarization. 105 New splice variants were also identified in members of the autophagy-related gene 8 (ATG8) family (LC3B, GABARAP and GABARAPL1).…”
Section: Emerging Implication Of Alternative Splicing In the Regulatimentioning
confidence: 99%
See 1 more Smart Citation
“…102,103 AS converts BECN1 from an inducer of nonselective macroautophagy to a regulator of mitochondriaselective autophagy. 105 BECN1s, a shorter splice variant originating from skipping of exons 10 and 11, selectively localizes in the outer membrane of mitochondria and contributes to mitophagy in response to starvation or mitochondrial membrane depolarization. 105 New splice variants were also identified in members of the autophagy-related gene 8 (ATG8) family (LC3B, GABARAP and GABARAPL1).…”
Section: Emerging Implication Of Alternative Splicing In the Regulatimentioning
confidence: 99%
“…105 BECN1s, a shorter splice variant originating from skipping of exons 10 and 11, selectively localizes in the outer membrane of mitochondria and contributes to mitophagy in response to starvation or mitochondrial membrane depolarization. 105 New splice variants were also identified in members of the autophagy-related gene 8 (ATG8) family (LC3B, GABARAP and GABARAPL1). 106 They encode proteins that are not integrated in the autophagosomes, suggesting that they could limit autophagy.…”
Section: Emerging Implication Of Alternative Splicing In the Regulatimentioning
confidence: 99%
“…Mitophagy, which refers to the selective removal of damaged or unwanted mitochondria, is crucial for mitochondrial quality control following stresses such as starvation, photo damage, hypoxia, and ROS production [15]. Certain physiological stresses can induce mitochondrial damage, which can cause oxidative stress and cell death triggered by the production of ROS from the mitochondrial electron transport chain (ETC).…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that phenomena of Beclin‐1 exclusive cleavage/splice, that could be a short noval varient of Beclin‐1, results in the subsequent formation of both the Beclin‐1‐PI3KC3 complex and its derivative, which are autophagic. BH3 domain of Beclin‐1 subsequently interacts with Bcl‐2 protein and act as anti‐apoptotic feature.…”
Section: Discussionmentioning
confidence: 99%